KOSOVA/O AND THE CHALLENGES OF RECOGNITION - Rrahmani, Bashkim (European Scientific Journal, ESJ, 2014)
Kosova si a new state in the Balkans created during the process of dissolution of the former Yugoslavia. The creation of this new state was very difficult and complicated, as well. This from both perspectives: internationally and locally. The process of Kosova independence differes from the approaches we may have, but we all agree that it was a difficult process and that Kosova would not have achieved independence, without strong international engagement. The project/ion of Kosova independence is not a pure Kosovar Albanian projection. It is also an international project as well, at least to a determined extent. Kosova since its Declaration of Independence has been recognized by a considered number of states but still the challenges of recognition are being met by Kosova people and Kosova institutions. International Community regarding the right of Kosova to self determination was split to some extent whereas also we could see different approaches within the academia and scholars regarding the right to self determination of Kosova. This has made the process of Kosova recognition to be a difficult process from international perspectives even though Kosova is already recognized from more than 100 states of the World.In addition International Court of Justice didn’t find Kosovo Declaration of Independence violating the International Law. Kosova institutions also have not shown to be enough strong in the process of lobbying for more recognitions. Therefore needs for recognitions are crucial and Kosova institutions have still a task to ensure as much as possible recognitions using arguments about the right of Kosova to self determination and explaining that Kosova is a sui generis case that can not be a precedent for other people aspiring self determination.